Andragogy as Theoretical Basis of Corporate Training in American Companies - Ogienko, Olena; Lytovchenko, Iryna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article analyzes the andragogical foundation of the organization of the learning process in American companies, particularly highlights the issues of andragogy as most commonly known theory of adult learning, the specific features of andragogical model of adult learning and ways of its application in corporate training in the Unites States.
Keywords: andragogy; andragogical model; corporate training (learning); adult learning principles; adult learning process; American companies